MAQASHID AL-SYARI’AH DALAM BINGKAI PENDIDIKAN - Khairul Mufti |Rambe (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2019)
The article seeks to reveal problems faced by Islamic education from theperspective of Maqâsid al-Sharîʻah, namely ideological (hifzal-dîn),practical (hifzal-nafs), academic (hifzal-‘aql), relationships or networks(hifzal-nasl), vocational (hifzal-mâl) and quality (hifzal-‘ird) aspects. Inorder to know the details of crucial problems of the Islamic education alongwith their alternative solutions, this paper suggests that the Islamiceducation should consider the insider’s and outsider’s perspective which hasfour types of roles as follow: a) complete observer; b) observer as participant;c) participant as observer; d) complete participant. This article proposesthree important implications, are: first, the problems of the Islamic educationcan be categorized and mapped based on Maqâsid al-Sharîʻah, in order toease the analysis of such problems. Second, the analysis of the problemsshould be based on the insiders’ and outsiders’ point of views, so that itwould be able to comprehensively detect the problems of Islamic educationand show the inclusiveness of the Islamic education. Third, problem solvingalternatives should be oriented at the level of theological (faith and religious[îmân]), theoretical (philosophical and empirical [‘ilm]), practical (learningand teaching [‘amal]) and moral (ethics and aesthetics [akhlâq]) realms.